Essays on Automation, Inequality, and Macroeconomic Performance - Koru, Ömer Faruk (online, 2021)
In the first chapter, I provide a theory that links automation to the top income inequality. I construct a model in which managing labor is harder than managing capital. Hence, an improvement in automation enables entrepreneurs to scale up their production. This leads highly productive entrepreneurs to capture a larger fraction of the market and hence this increases top income inequality. I show that the shape parameter of the Pareto distribution that characterizes the right tail of income distribution is inversely related to the automation parameter. Using cross-industry and cross-country data, I provide empirical support for the model's prediction.In the second chapter, I quantitatively analyze the impact of improvements in automation technology on top wealth shares. I incorporate the production function that I consider in the first chapter into an Aiyagari model with entrepreneurs and a financial friction. An improvement in automation technology impacts wealth concentration through two channels: first, it increases the return to entrepreneurial skill; second, it increases dispersion to return to capital. I calibrate the model to the 1968 US economy and increased the automation parameter to the 2016 value. Comparing the two steady-states, the model generates one-fourth of the observed increase in wealth share of the top 1% and explains 10% of the observed increase in the top 0.1%. In consumption equivalence terms, workers' welfare increases by 5%, and entrepreneurs' welfare increases by 8%. The third chapter examines the strong positive correlation between job-to-job transition rates and nominal wage growth in the U.S. First, using time series regressions, structural monetary policy shocks, and survey data on search effort we provide evidence that inflationary shocks cause higher job-to-job transitions in the subsequent years. Second, we build a model with aggregate shocks and competitive on-the-job search in which wages react sluggishly to inflation. Third, we calibrate the model to the U.S. economy and find that the output response to inflation shock is non-monotonic. The monetary authority can stimulate productivity with an inflationary shock through job-to-job transitions.
Keywords: Graue Literatur; Hochschulschrift; Aufsatzsammlung; Income inequality; Equilibrium; Quantitative analysis; Efficiency; Income distribution; Business income; Monetary policy; Labor market